Methodological limitations in studying the effect of (inter)ethnicity on voting behaviour, with examples from Bulgaria, Romania, and Slovakia - Zamfira, Andreea (ERDKUNDE, 2015)
This article is based on an empirical multi-country analysis and on a systemic theoretical research on how the (inter)ethnic factor influences voting behaviour. The multi-ethnic regions from Bulgaria, Romania, and Slovakia included in this study differ significantly across a spectrum of political, social, and economic characteristics. However, they are similar with respect to one particular aspect – the historic cohabitation of two or more distinct cultures. Examining the diverse backgrounds and traditions of political science and sociology, this paper attempts to show how ethnicity and, implicitly, interethnicity, both objectively and subjectively constructed, influence political behaviour in the given regions. Despite the obvious complexity of determination systems specific to multi-ethnic communities, so far little research has focused on the impact of ethnicity and interethnicity on political behaviours in general and on voting behaviour in particular. Electoral studies continue to focus on traditional “ethnic solidarities”, a thesis that is often contradicted by empirical findings and, as a matter of fact, by the present research. The article concludes by reflecting critically on the current mechanical models of analysis, which are based on a simplistic understanding of ethnicity and ethnic minorities’ identities. At the same time, it questions the methodological limitations in explaining the atypical cases of non-ethnic voting.